Development of food allergies in patients with Gastroesophageal Reflux Disease treated with gastric acid suppressive medications. Issue 6 (2nd August 2013) - Trikha, Anita; Baillargeon, Jacques G.; Kuo, Yong‐fang; Tan, Alai; Pierson, Karen; Sharma, Gulshan; Wilkinson, Gregg; Bonds, Rana S.
Abstract: Background: The prevalence of food allergy has steadily increased, especially in children. Reflux disease, a very common problem in children, is often treated with gastric acid suppressive (GAS) medications which may alter the processing of food allergens, thereby affecting oral mucosal tolerance. Objective: The purpose of this study was to determine if use of GAS medications is associated with the occurrence of food allergies in children. Methods: Using a large national commercial insurance database, we identified 4724 children aged 0–18 yrs who were diagnosed with Gastroesophageal Reflux Disease (GERD) and treated with GAS medications between January 1, 2008 and September 30, 2009. We then matched 4724 children with GERD not treated with GAS medications and 4724 children without GERD and not treated with GAS medications, at a 1:1 ratio, on age, gender and number of atopic risk factors. Patients were followed for 12 months. Results: In comparison to the referent (children without GERD who received no GAS medications), children with GERD who were treated with GAS were more likely to be diagnosed with a food allergy (Hazard ratio (HR): 3.67, 95% CI 2.15–6.27), as were children with GERD diagnosis but who were not treated with GAS medications (HR: 2.15, 95% CI: 1.21–3.81). A direct comparison of the two GERD cohorts showed that children with GERD who were treated with GAS had a greater risk of food allergy than those with GERD who were untreated (HR, 1.68, 95%CI, 1.15–2.46). Conclusion: Treatment with GAS medications is associated with the occurrence of food allergy, an effect not apparently related to a diagnosis of GERD alone.